THE EFFECT OF RETURN ON ASSETS AND DEBT TO ASSETS RATIO ON TAX AVOIDANCE IN PLANTATION COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2016-2018 PERIOD - Sucipto, Tia Novira; Hasibuan, Renika (Accounting and Business Journal, 2020)
For tax companies it is a burden that will reduce net income so that many companies are trying to find ways to minimize the tax burden that does not violate the law, commonly referred to as tax avoidance, this study aims to determine the effect of Return On Assets and Debt to Assets Ratio on avoidance. The sampling technique used was purposive sampling, the final sample size was 10 plantation companies listed on the Indonesia Stock Exchange in 2016-2018. The analysis method used is multiple linear regression analysis of panel data using SPSS 24.00. Based on the research results, it shows that the Return on Assets and Debt to Assets Ratio have a significant effect on tax avoidance. It is recommended for further research if you want to follow up on Return On Assets, Debt to Assets Ratio and tax avoidance or with similar research topics can be expected to add other variables, such as variables of liquidity and company size. Management is expected to be able to manage all of its total assets and control interest expenses and minimize tax burdens each year so that the profit earned by the company increases every year.